Circulating sepsis-related metabolite sphinganine could protect against intestinal damage during sepsis - Wang, Zetian; Qi, Yue; Wang, Fei; Zhang, Baiyin; Jianguo, Tang (Frontiers in Immunology, 2023)
Sepsis is intricately linked to intestinal damage and barrier dysfunction. At present times, there is a growing interest in a metabolite-based therapy for multiple diseases. Herein, we collected serum samples from septic patients and healthy individuals, and assessed their metabonomics profiling using Ultra-Performance Liquid Chromatography-Time of Flight Mass Spectrometry (UPLC-TOFMS). The eXtreme Gradient Boosting algorithms (XGBOOST) method was used to screen essential metabolites associated with sepsis, and Sphinganine and Mannose 6-phosphate were identified as the best set of variables. Further more, five machine learning models, including Logistic Regression, XGBoost, GaussianNB(GNB), upport vector machines(SVM) and RandomForest, were constructed to distinguish sepsis including a training set and validation set, and were then evaluated in the rest of the study sample. The area under the receiver-operating characteristic curve (AUROC) and Brier scores were used to compare the prediction performances of different models. Finally, the XGBOOST(AUROC=0.956) model was used to predict spesis. The SHapley Additive exPlanations (SHAP) package was used to interpret the XGBOOST model. Pearson analysis reinforced the expression of Sphinganine, Mannose 6-phosphate were positively associated with the Acute Physiology and Chronic Health Evaluation-Ⅱ(APACHE-Ⅱ) score, Procalcitonin(PCT), White blood cell, C-reactiveprotein(CRP), and Interleukin-6(IL-6). Subsequently, we tested LPS-induced Caco-2 cell viability using the LDH release assay, which revealed that sphinganine offered strong protection to the injured Caco-2 cells. Using both cellular and animal models, we revealed that sphinganine directly inhibited inflammation, while promoting intestinal tight junction protein synthesis, which, in turn, protected against sepsis-induced intestinal barrier damage. Collectively, these findings highlighted the potential diagnostic value of the ML, and also provided new insight into enhanced therapy and/or preventative measures against sepsis